2021
DOI: 10.3390/ani11030821
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Hair-Cortisol Concentration and Various Welfare Assessments of Dutch Dairy Farms

Abstract: Many protocols have been developed to assess farm animal welfare. However, the validity of these protocols is still subject to debate. The present study aimed to compare nine welfare assessment protocols, namely: (1) Welfare Quality© (WQ), (2) a modified version of Welfare Quality (WQ Mod), which has a better discriminative power, (3) WelzijnsWijzer (Welfare Indicator; WW), (4) a new Welfare Monitor (WM), (5) Continue Welzijns Monitor (Continuous Welfare Monitor; CWM), (6) KoeKompas (Cow Compass; KK), (7) Cow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Hence, we recommend using the simplest formula for WI (i.e., without the Cm term, which is assumed to equal one). The simplification of the original WQ protocol into our WI has recently been shown to result in a better match with five other (i.e., non-WQ based) dairy herd welfare assessment metrics used in the Netherlands and with the consensus herd welfare score given by at least five dairy cattle veterinarians that visited the farms on a regular basis (40). These findings thus provide some support for an improved concurrent and consensus validity, respectively, of the WI as compared to the original WQ overall categorization.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we recommend using the simplest formula for WI (i.e., without the Cm term, which is assumed to equal one). The simplification of the original WQ protocol into our WI has recently been shown to result in a better match with five other (i.e., non-WQ based) dairy herd welfare assessment metrics used in the Netherlands and with the consensus herd welfare score given by at least five dairy cattle veterinarians that visited the farms on a regular basis (40). These findings thus provide some support for an improved concurrent and consensus validity, respectively, of the WI as compared to the original WQ overall categorization.…”
Section: Discussionmentioning
confidence: 99%
“…McGreevy et al, 2018), and the Quality of Life (e.g., Green and Mellor, 2011), approaching animal welfare from different points of view (see Webster, 2016). Unfortunately, the correlation between assessment tools derived from these (and other) concepts (e.g., Andreasen et al, 2013) and their consistency over time may be weak (Knierim and Winckler, 2009;van Eerdenburg et al, 2021), indicating the necessity for more research to derive well validated and useful welfare assessment tools.…”
Section: Assessing Animal Welfare Based On Dawconmentioning
confidence: 99%
“…Previous studies on cattle have shown increased levels of hair cortisol in clinically compromised cows and cows subjected to heat stress (Burnett et al, 2015;Ghassemi Nejad et al, 2017). However, only weak associations between the results of welfare assessments and HCC in dairy cows have been observed at the herd level (van Eerdenburg et al, 2021).…”
Section: Introductionmentioning
confidence: 98%